2014
DOI: 10.1590/1807-3107bor-2014.vol28.0059
|View full text |Cite
|
Sign up to set email alerts
|

Delayed tooth replantation: MTA as root canal filling

Abstract: MTA has been investigated as a root-end filling material. Its mechanism of action has some similarities to that of Ca(OH) 2 . The purpose of this study was to evaluate the repair process taking place in the delayed replantation of monkey teeth using calcium hydroxide and MTA as root canal filling materials. Five monkeys had their lateral incisors extracted and bench-dried for 60 minutes. After root canal preparation, the teeth were assigned to two groups according to root canal filling material: I, calcium hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…, Panzarini et al . , Esteves et al . ), a number of case reports reported the successful treatment of inflammatory root resorption by placing either MTA or CEM cement as root filling materials following unsuccessful treatment with calcium hydroxide as a medicament an attempt to arrest inflammatory resorption (Aggarwal & Singla , Güzeler et al .…”
Section: Resorptionmentioning
confidence: 98%
See 2 more Smart Citations
“…, Panzarini et al . , Esteves et al . ), a number of case reports reported the successful treatment of inflammatory root resorption by placing either MTA or CEM cement as root filling materials following unsuccessful treatment with calcium hydroxide as a medicament an attempt to arrest inflammatory resorption (Aggarwal & Singla , Güzeler et al .…”
Section: Resorptionmentioning
confidence: 98%
“…Several animal studies on primates and rats evaluated the effect of root filling or the placement of an apical plug of MTA Angelus, MTA Fillapex, white MTA Angelus and calcium hydroxide in teeth with immediate and delayed replantation (Panzarini et al . , , Marão et al . , Esteves et al .…”
Section: Resorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 They have excellent sealing property and biocompatibility. 24 Panzarini et al 25 demonstrated smaller areas of ankylosis when MTA was used as root filling material in comparison with CH, in a study involving delayed replantation of teeth in monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, a pasta à base de hidróxido de cálcio foi utilizada, no presente estudo, como medicação intra-canal em todos os grupos, por simularem um reimplante tardio, tendo em vista que a medicação poderia ser somente introduzida no canal radicular de maneira retrógrada. No entanto, em um estudo mais recente que avaliou o processo de reparo, após reimplante tardio em dentes de macaco obturados com hidróxido de cálcio e MTA, foi demostrada uma maior ocorrência de anquilose nos dentes obturados com hidróxido de cálcio (Panzarini et al, 2014b).…”
Section: Classificação Da Reabsorção Dentáriaunclassified